A Review of Information Technologies Used in Health Care on the Example of Treatment of Haemophilia Patients - Topolski, Przemysław; Greńczuk, Andrzej (Przegląd technologii informacyjnych wykorzystywanych w ochronie zdrowia na przykładzie chorych na hemofilię, 2024)
Objective: Discussion information technologies and tools that can be used in health care in Poland in the field of haemophilia treatment. Methods: The research was conducted through participant observations and analysis of existing technologies. Results: The existing development of IT systems may contribute to helping in the treatment of haemophilia and facilitating functioning with the disease in question by creating dedicated IT systems, implementing already available technologies and using new solutions. In this regard, augmented reality (AR) and the Metaverse can be used to create IT systems to support patients and medical staff in agent administration training. Implications and recommendations: The publication overviews current solutions and aims to indicate the direction of using new technological solutions. In practical terms, the work defines the directions that can be used in augmented reality and the Metaverse. Originality/value: The value of the work is the analysis of the medical issue from the point of view of management and quality sciences. In addition, it has been expanded to include an analysis of technological solutions.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 94-105
Keywords: haemophilia; information system; augmented reality; Metaverse; medical care; hemofilia; systemy informatyczne; rozszerzona rzeczywistość; Metawerse; opieka medyczna